Pronoun (Ù€ Ù‰) from the Grammatical and Semantic point of view in Bahdini Sub Ù€ Dialect - Ameen, Sheleer (Humanities Journal of University of Zakho, 2022)
The search entitled as “ Pronoun (ـ ى) from the Grammatical and Semantic point of view in Bahdini Sub ـ Dialect ” (ى) is a type of pronoun that continuously refers to a nominative phrase that is mentioned in the previous sentences. According to transformational grammar, the occurrence of (ى) in the sentence makes it a derivative component, and its appearance is according to one of the optional transformative grammar rules called substitution. (ـ ى) has an important role in the process of deriving new lexical concepts, in addition to being a type of reference, and it is effective in the process of referring to the preceding (Anaphora). The research consists of two chapters in addition to the conclusion and a presentation of the most important results that were reached at the end of the research, and the study was carried out according to the descriptive method.